Disease prevalence and bacterial isolates associated with Acropora palmata in the Colombian Caribbean - Garzon-Machado,Marco; Luna-Fontalvo,Jorge; García-Urueña,Rocio (PeerJ, 2024)
The decline in Acropora palmata populations in Colombian reefs has been mainly attributed to diseases outbreaks. The population size structure and prevalence of white pox and white band disease were evaluated in six localities of the Colombian Caribbean. Here, we aimed to isolate enteric bacteria and Vibrios from healthy and diseased coral mucus to relate its presence to the health status of Acropora palmata. The isolated bacteria were identified using molecular analyses with the 16S rRNA gene. Larger colonies had the highest percentage of the prevalence of both diseases. The strains that were identified as Vibrio sp. and Bacillus sp. were common in the healthy and diseased mucus of the holobiont. The Exiguobacterium sp. and Cobetia sp. strains isolated from diseased mucus may indicate maintenance and resilience mechanisms in the coral. Enterococcus sp. and other bacteria of the Enterobacteriaceae family were isolated from some localities, suggesting that probably contamination due to poor treatment of domestic wastewater and contributions from river discharges can affect coral health. The spatial heterogeneity of Colombian coral reefs exhibited variability in the bacteria, wherein environmental alterations can trigger signs of disease.
Keywords: Coral disease; Holobiont; Endangered species; Acropora palmata; Bacterial isolates